2022
DOI: 10.1021/acs.orglett.2c02904
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Cryptic Bifunctional Type I Diterpene Synthase Involved in Talaronoid Biosynthesis from a Marine-Derived Fungus

Abstract: We report the identification of the tnd biosynthetic cluster from the marine-derived fungus Aspergillus flavipes and the in vivo characterization of a cryptic type I diterpene synthase. The heterologous expression of the bifunctional terpene synthase led to the discovery of a diterpene backbone, talarodiene, harboring a benzo[ a ]cyclopenta[ d ]cyclooctane tricyclic fused ring system. The conversion of geranylgeranyl di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…avipes CNL-338 is the only example that proceeds through a type-c cyclization cascade, which forms the 5/8/6 tricyclic diterpene talarodiene (54). 81 The cyclization from G + involves ring expansion to form G-8 + . Subsequent C10 deprotonation and reprotonation at C2 generate G-9 + , which then undergoes 1,2-hydride transfer and C2-C6 cyclization to form G-10 + .…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…avipes CNL-338 is the only example that proceeds through a type-c cyclization cascade, which forms the 5/8/6 tricyclic diterpene talarodiene (54). 81 The cyclization from G + involves ring expansion to form G-8 + . Subsequent C10 deprotonation and reprotonation at C2 generate G-9 + , which then undergoes 1,2-hydride transfer and C2-C6 cyclization to form G-10 + .…”
Section: Reviewmentioning
confidence: 99%
“…Deprotonation of G-10 + at C8 yields 54 (Scheme 8). 81 2.1.3.3 Diterpene cyclases with type-d cyclization mechanism. The cyclization cascades of the terpenoid cyclases with typed cyclization mechanism from cation G + proceed through two successive WMR via ring expansion and contraction to form cation G-11 + .…”
Section: Reviewmentioning
confidence: 99%
“…3 The crystal structure and cyclization mechanism of PaFS have been extensively studied, offering deep insights into the enzymatic facilitation of 5−8−5 skeleton formation. 4 Building upon the foundational understanding on PaFS, our previous research introduced TndC, 5 the first diterpene synthase identified to facilitate the formation of the diterpene talarodiene with a 5−8−6 skeleton, marking a significant stride in the field. However, the in vitro functionality and detailed cyclization mechanism of TndC remain largely unexplored, opening a vista of opportunities for further research.…”
mentioning
confidence: 99%
“…Upon normal-phase high-performance liquid chromatography (HPLC), two new products ( 1 and 2 ) were observed in the metabolites from AO- tlnA (Figure B). The major product ( 1 ) was identified as talarodiene, and the minor product ( 2 ) was confirmed as a new product; their structures were determined on the basis of the nuclear magnetic resonance (NMR) data (Figures S13–S20). Then, we prepared a recombinant TlnA protein in Escherichia coli for an in vitro enzymatic reaction.…”
mentioning
confidence: 99%
“…The gene cluster responsible for the biosynthesis of talaronoid C 28 has been characterised from the marine-derived fungus Aspergillus flavipes . 24 Heterologous expression of cryptic bifunctional type I diterpene synthase from this pathway identified talarodiene 29 as an intermediate of talaronoid C biosynthesis.…”
mentioning
confidence: 99%